Manual Vacuum Aspiration Versus Dilatation and Curettage for Treatment of 1st Trimester Miscarriage - Zill-E-Huma, Amna Asif, Shagufta Jabbar, Ghazala Iftikhar, Kamran Ullah Khan, Asma Hanif, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Miscarriage in the first trimester contributes for the most pregnancy losses. Manual vacuum aspiration (MVA) or manual suction curettage is a method of uterine evacuation that allows women with first trimester miscarriage to be safely treated in the Outpatient department or Emergency department instead of Operation theatre. Office-based treatment reduces costs for both the client and the health system. Objectives: To determine the effectiveness, safety and frequency of patients’ satisfaction undergoing manual vacuum aspiration versus dilatation and curettage (DNC) for treatment of 1st trimester miscarriage. Methods: This observational study was conducted in Gynecology department of Social Security Teaching Hospital, Lahore over a period of 1 year from 15-06-2022 to 14-06-2023. A total of 200 cases were included and 100 cases were assigned to each group undergoing MVA or dilatation and curettage (DNC) randomly. Procedure of MVA was performed in examination room under para-cervical block whereas dilatation and curettage was performed in theatre under anesthesia. The efficacy, complications and patients’ satisfaction were determined for both procedures. Results: Manual vacuum aspiration was superior in terms of shorter hospital stay (3.3±0.9 vs 6.14±2.64 hours; p=0.001) and less duration of procedure. Absolute evacuation was attained in 98% with Manual suction curettage versus 90% with dilatation and curettage. Uterine perforation (2%), post procedure infection(2%)and pain abdomen(7%) were encountered in dilatation and curettage group. 98% women were satisfied with MVA as compared to dilatation and curettage where 94% women were satisfied. Conclusion: Manual vacuum aspiration is as effectual as dilatation and curettage for treatment of first trimester miscarriage while being cheap, efficient and quick, has less hospital confinement and leads to slighter blood loss and complications as compared to dilatation and curettage. Keywords: 1st trimester miscarriage, Manual vacuum aspiration, Dilatation and curettage, Satisfaction.